MEMBANGUN LINGKUNGAN PENDIDIKAN AGAMA DALAM KELUARGA MENURUT PERSPEKTIF AL-QUR'AN - lutfi lutfi (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
Relationships between individuals in the family environment greatly affect the child's mental health and its effects will be seen until later when he reaches adulthood. A loving and conducive atmosphere for intellectual development that is successfully built in a family will enable a child to be able to apply religious teachings in his life, and be able to also adapt to himself, with his family and with the surrounding community. Therefore, in the process of forming a family, an integrated and guided religious education program is needed. The religious education program in the family must also be able to provide clear work descriptions for each individual in the family so that each can carry out a continuous role for the creation of an Islamic family environment that is conducive to educating children to the fullest